The beginnings of nursing in Mexico: Conflicts of power and gender, 1896-1904 - Douglas C. Nance (Cultura de los Cuidados, 2018)
At the beginning of secular nursing in Mexico the career was involved in conflicts of power, role and gender with medicine.